Morfologia de conídios e patogenicidade de isolados de Exserohilum turcicum da Argentina e do Brasil em milho - De Rossi, Roberto Luis (2014)
Corn crop is one of the most important commodities in Argentina and Brazil. Its yield is reduced by different pathogens such as Exserohilum turcicum (Et), the causal agent of Northern leaf blight in corn. This study aimed to compare the morphological characteristics of conidia and the pathogenicity of ten Et isolates obtained from Argentina and Brazil. Five monosporic isolates from each country were cultured on lactose casein hydrolysate agar (LCHA) for 15 days at 25 ± 2ºC in the absence of light. Microscopic slides were prepared to measure 200 conidia of each isolate. On average, conidia measured 10-25 x 30-135 µm, presenting 2-8 septa. Statistical differences (p = 0.05) were detected among the 10 Et isolates for all measured variables (length, width and number of septa). Despite such variation, the recorded characteristics coincided with those reported in the literature. For pathogenicity tests, corn hybrid plants Pioneer P1630H, of known susceptibility to Et, were inoculated by the deposition of 0.5 ml of an Et conidial suspension at the concentration of 5x104 conidia/mL, in the whorl, when the fourth leaf was expanded. All ten isolates produced, after the 15 days of inoculation, an average of 2.5 lesions/leaf, of 39.7 x 3.4 mm length and width, respectively, and 4% estimated severity. There were no significant differences in the pathogenicity of all ten studied isolates for any of the pathometric criteria. There were morphological differences between isolates from Argentina and Brazil but not in pathogenicity. This confirms that the isolates used in this study belong to the species Et.